Does moderate intensity exercise attenuate the postprandial lipemic and airway inflammatory response to a high-fat meal? - Kurti, Stephanie P.; Rosenkranz, Sara K.; Levitt, Morton; Cull, Brooke J.; Teeman, Colby S.; Emerson, Sam R.; Harms, Craig A. (My University, 2015)
We investigated whether an acute bout of moderate intensity exercise in the postprandial period attenuates the triglyceride and airway inflammatory response to a high-fat meal (HFM) compared to remaining inactive in the postprandial period. Seventeen (11 M/6 F) physically active (≥150 min/week of moderate-vigorous physical activity (MVPA)) subjects were randomly assigned to an exercise (EX; 60% VO[subscript 2peak]) or sedentary (CON) condition after a HFM (10 kcal/kg, 63% fat). Blood analytes and airway inflammation via exhaled nitric oxide (eNO) were measured at baseline, and 2 and 4 hours after HFM. Airway inflammation was assessed with induced sputum and cell differentials at baseline and 4 hours after HFM. Triglycerides doubled in the postprandial period (~113 ± 18%, P < 0.05 ), but the increase did not differ between EX and CON. Percentage of neutrophils was increased 4 hours after HFM (~17%), but the increase did not differ between EX and CON. Exhaled nitric oxide changed nonlinearly from baseline to 2 and 4 hours after HFM (P < 0.05, ƞ² = 0.36) . Our findings suggest that, in active individuals, an acute bout of moderate intensity exercise does not attenuate the triglyceride or airway inflammatory response to a high-fat meal.
Citation: Stephanie P. Kurti, Sara K. Rosenkranz, Morton Levitt, et al., “Does Moderate Intensity Exercise Attenuate the Postprandial Lipemic and Airway Inflammatory Response to a High-Fat Meal?,” BioMed Research International, vol. 2015, Article ID 647952, 10 pages, 2015. doi:10.1155/2015/647952